Withaferin A Inhibits Nuclear Factor-κB-Dependent Pro-Inflammatory and Stress Response Pathways in the Astrocytes - Francesca Martorana; Giulia Guidotti; Liliana Brambilla; Daniela Rossi (Neural Plasticity)
Several lines of evidence suggest that astrocytes play a key role in modulating the immune responses of the central nervous system (CNS) to infections, injuries, or pathologies. Yet, their contribution to these processes remains mostly elusive. Astroglia are endowed with a wide range of toll-like receptors (TLR) by which they can sense infectious agents as well as endogenous danger signals released by damaged cells. Here we demonstrate that the activation of astrocytic TLR4 by bacterial lipopolysaccharide (LPS) challenge can promote nuclear factor κB (NF-κB)-dependent induction of pro-inflammatory and stress response mediators, particularly Tumor Necrosis Factor α (TNFα), cyclooxygenase 2 (COX-2), and inducible nitric oxide synthase (iNOS). Since the steroid lactone Withaferin A was described to inhibit NF-κB activity in different cell types, we next determined the impact of this natural compound towards the identified astrocytic signalling pathway. Innate immune activation was induced by stimulation of the LPS/TLR4 axis in spinal cord astrocytes. We provide evidence that both pre-treating and post-treating the cells with Withaferin A attenuate astrocytic NF-κB activity as well as the consequent production of TNFα, COX-2, and iNOS induced by stimulation of the LPS/TLR4 pathway. This study suggests that Withaferin A may be an eligible candidate for the treatment of neuroinflammatory and stress conditions characterized by an important astrocytic input.